The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1093/ntr/ntr167
|View full text |Cite
|
Sign up to set email alerts
|

Primary Care Providers Advising Smokers to Quit: Comparing Effectiveness Between Those With and Without Alcohol, Drug, or Mental Disorders

Abstract: Introduction: Individuals with alcohol, drug, or mental (ADM) disorders combined make up over 40% of all smokers in the U.S. Primary care providers (PCPs) play an important role in smoking cessation counseling, but their effectiveness with this population is unclear. This study evaluated the effectiveness of PCP smoking cessation counseling for smokers with ADM disorders. Methods Results:Smokers with and without ADM disorders were equally likely to receive smoking cessation counseling (72.9% vs. 69.9%). Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…28 Moreover, recent health reforms have broadly supported the development of a value-based health system that emphasizes primary care while expanding access to cessation services that can be delivered by general medical providers. 29 Along with advising smokers to quit, general medical providers can prescribe evidence-based medications to assist with tobacco cessation or refer more complicated cases to specialty mental health and substance use providers. 30,31 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Moreover, recent health reforms have broadly supported the development of a value-based health system that emphasizes primary care while expanding access to cessation services that can be delivered by general medical providers. 29 Along with advising smokers to quit, general medical providers can prescribe evidence-based medications to assist with tobacco cessation or refer more complicated cases to specialty mental health and substance use providers. 30,31 …”
Section: Discussionmentioning
confidence: 99%
“…37 Establishing clear guidelines for payers and providers could mitigate financial challenges associated with reforming insurance coverage and reimbursement for cessation services. 29 Incorporating tobacco services and metrics into delivery and information systems could raise overall screening and counseling rates. 38 Further research is needed to characterize and overcome potential barriers to providing tobacco cessation services to groups with mental health and substance use problems in general healthcare settings and to identify priority areas to target for improvement.…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of including smoking cessation in detoxification programs may be twofold: first a reciprocal pharmacological gain from combining treatments and second, the possibility of extending the intervention to otherwise undertreated populations, similar to what done with drug abusers attending primary care visits (Ong, Zhou, & Sung, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been difficult to ensure that healthcare settings consistently provide evidence-based tobacco dependence treatment, even though these treatments can double or triple smokers' success rates [1]. While 80 % of smokers in the U.S. (almost 35 million people) see a primary care clinician each year and approximately 70 % want to quit smoking, fewer than half of smokers report being advised to quit by their primary care clinician in the past year, and only about 25 % receive evidence-based counseling and/or medication [3,4]. A recent population-based survey found that among smokers and smokers who had quit in the last 2 years, less than one third had used evidence-based treatment (counseling and/or medications [4]).…”
Section: Introductionmentioning
confidence: 99%